Mahwa al-Ummiyah al-Raqmiyyah: al-Atsar wa al-Tahaddiyyat wa al-Furash fi Ta’lim al-Lughah al-Arabiyyah / Digital Literacy: Impacts, Challenges and Opportunities in Arabic Language Education - Siti Rauhillah; Muhajirin Ramzi; Hamzah Hamzah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
The digital era requires academics and practitioners to carry out digital literacy. Digital literacy is a behavior or movement to adapt to digital through accessing, utilizing and developing digital media as a learning medium. Arabic is important to learn, therefore digital literacy in the field of Arabic language learning needs to be implemented. However, in the process there are many impacts, challenges and opportunities. This research is a literature study research by conducting searches through books and articles in cyberspace. To focus the problem, the aim of this research is to find out what digital literacy is, and what the challenges and impacts are in learning Arabic. The results of this research are: 1) the impact of digital literacy includes the impact on Arabic teachers, Arabic students and Arabic language learning, 2) The challenges are the influence of the use of Arabic language in the field of education and literacy, Western hegemony on works. Arabic works written by Muslim scientists, a bad impression about the Arabic language that occurs in this era of globalization, 3) The opportunity is to become a way to study with non-Arab people in an easy way, sparking and provoking the development of Arabic language research and learning , strengthening the translation of Arabic works for science and Islam, strengthening access and collaboration with external parties, Opportunities for developing Arabic language learning media.المستخلص: يتطلب العصر الرقمي من الأكاديميين والممارسين القيام بمحو الأمية الرقمية. محو الأمية الرقمية هو سلوك أو حركة للتكيف مع الرقمية من خلال الوصول إلى الوسائط الرقمية واستخدامها وتطويرها كوسيلة تعليمية. اللغة العربية مهمة للتعلم ، لذلك يجب تنفيذ محو الأمية الرقمية في مجال تعلم اللغة العربية. ولكن في هذه العملية هناك العديد من الآثار والتحديات والفرص. هذا البحث هو بحث دراسة الأدبيات من خلال البحث في الكتب والمقالات في الفضاء السيبراني. لتركيز المشكلة ، الغرض من هذه الدراسة هو معرفة ماهية محو الأمية الرقمية ، وما هي التحديات والآثار في تعلم اللغة العربية. نتائج هذه الدراسة هي 1) تأثير محو الأمية الرقمية يشمل التأثير على معلمي اللغة العربية وعلى الطلاب العرب وعلى تعلم اللغة العربية، 2) التحديات هي تأثير استخدام اللغة العربية العمية في مجالات التعليم ومحو الأمية ، والهيمنة الغربية على الأعمال العربية التي كتبها العلماء المسلمون ، والصورة السيئة للغة العربية التي تحدث في عصر العولمة هذا, 3) الفرصة هي أن تكون وسيلة للتعلم مع غير العرب بطريقة سهلة ، وإثارة وإثارة تطوير البحث والتعلم باللغة العربية ، وتعزيز ترجمة الأعمال العربية للعلم والإسلام، وتعزيز الوصول والتعاون مع الأطراف الخارجية ، فرص لتطوير وسائل الإعلام التعليمية العربية.